2018
DOI: 10.1186/s40100-018-0101-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of farmer education on farm productivity under varying technologies: case of paddy growers in India

Abstract: This paper analyzes the effects of education on farm productivity in the case of growers of modern and traditional varieties of paddy in Odisha, Eastern India. Using an endogenous switching regression model, the study has found that a minimum threshold level of education is significantly influencing the adoption of modern varieties of paddy and thereby the farm productivity of adopters only. So, the study finds the evidence in support of Schultz hypothesis that says education enhances farm productivity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 38 publications
10
75
1
3
Order By: Relevance
“…Well educated farmers first are capable of using available information more competently, second, they have better access to required information and, third, they are more likely to adopt new technologies or products earlier since they have superior access to related information, are more capable of distinguishing between promising and unpromising innovations, and are more willing to adopt riskier production technologies if these technologies provide higher expected returns. Education is usually proxied by years of schooling or a dummy variable showing a minimum threshold level [44], as both these approaches measure the quantity of schooling and hence the level of education [45]. In this paper we control for both general and agricultural specific education.…”
Section: Data and Descriptive Analysismentioning
confidence: 99%
“…Well educated farmers first are capable of using available information more competently, second, they have better access to required information and, third, they are more likely to adopt new technologies or products earlier since they have superior access to related information, are more capable of distinguishing between promising and unpromising innovations, and are more willing to adopt riskier production technologies if these technologies provide higher expected returns. Education is usually proxied by years of schooling or a dummy variable showing a minimum threshold level [44], as both these approaches measure the quantity of schooling and hence the level of education [45]. In this paper we control for both general and agricultural specific education.…”
Section: Data and Descriptive Analysismentioning
confidence: 99%
“…Increasing formal and informal education would increase the ability to handle chicken and to apply the management practice of the chicken rearing business. Thus, the farmers who completed minimum education at the secondary level are most likely to adopt new technology and experience the yield augmenting effects of education (Paltasingh and Goyari, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Owuor et al (2020) reported that education impacts agricultural output through supporting farmer adoption of new productivity enhancing technologies. Paltasingh and Goyari (2018) found that a minimum threshold level of education is significantly influencing the adoption of modern varieties of paddy and thereby the farm productivity of adopters only. Weir (1999) reported that education enhances the farming skills and productive capabilities of the farmers.…”
Section: Socio -Demographic Characteristics Of Respondentsmentioning
confidence: 99%